NONLINEAR PERTURBATION METHOD FOR CALCULATING AXISYMMETRIC CAVITATIONAL FLOWS - Buivol, Vasyl (Proceedings of National Aviation University (archive), 2014)
A mathematical model of a cavity under the influence of perturbations of various origins is evaluated. The model is based on hydrodynamics of flows with free boundaries and the theory of small perturbations. Specific analysis is provided for cavitational flows behind cones